Intelligence information within criminal proceedings - Adrián Vaško (DANUBE: Law, Economics and Social Issues Review, 2019)
The purpose of this article is to study the possibility of using intelligence in criminal proceedings in the Slovak Republic. The author examines the current legislation related to the examined issue in the context of criminal procedural law. The aim of the study is to analyze and justify the possibility of using intelligence in criminal proceedings, especially in the taking of evidence. In the context of the current security challenges, this is a serious issue which is currently relatively little developed in theory. The author concluded that the use of intelligence information is possible and applied in criminal proceedings in the Slovak Republic. This is justified by the specific provisions of the legislation in force and by the case-law of the European Court of Human Rights. In this context, it can be expected that the importance of intelligence in criminal proceedings will increase.
Keywords: 330; Proceedings; Taking Evidence; Intelligence; Intelligence Information